The Influence Of Work Ethic And Work Attitude On Employee Performance At The Golden Sriwijaya Building Company Palembang - Sartika, Wiwin; Ermeila, Sri; Aryanti, Rahmi (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This study aims to examine the influence of work attitude and work ethic on employee performance at a company in the Golden Sriwijaya Building, Palembang. The background of this study is based on the importance of attitude and work ethic in improving individual performance in the workplace. The study employs a quantitative approach, with data collected through initial interviews with one employee and the distribution of questionnaires to 41 respondents. Data analysis was conducted using multiple linear regression. The results indicate that work attitude and work ethic simultaneously have a significant impact on employee performance, contributing 28.0%, while 72.0% is influenced by other factors. The calculated F-value of 7.391 > the critical F-value of 2.46, and the significance level of 0.002 < 0.005, leading to the rejection of H₀ and the acceptance of H₁. These findings indicate that work attitude and work ethic play a crucial role in improving employee performance.